RELAKSASI DENGAN AROMATERAPHY LEMON UNTUK MENGURANGI MUAL MUNTAH PADA MASA KEHAMILAN TRIMESTER I - Nur Sa’idah; Sthepani Sari Hidayat; Siti Kholifatul Marhamah; Hanik Rosida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Pregnancy is a stage that will make a change to the mental, physical, and social which is influenced by various factors, one of the first symptoms of a pregnancy. Nausea and vomiting of pregnancy is generally called morning sickness, experienced by about 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. Lemon essential oil (citrus lemon) is one of the herbal oils that is considered a safe drug in pregnancy. This study aims to determine the effect of inhalation of lemon aromatherapy on nausea and vomiting in pregnant women. The method used in this study is to search for analytical data by using a literature review by looking for relevant journals or articles. The source of the review uses electronic media from various databases including Google Scholar and Sience Direct which are published in the period 2018-2022, in the form of research journals and articles. review of 5 journals. The writing of this scientific article uses the APA bibliography writing. The population in this study were first trimester pregnant women who experienced nausea and vomiting. From the results of the study, there was an effect of giving lemon aroma therapy to nausea and vomiting in pregnant women. Therefore, it is recommended that pregnant women who experience nausea and vomiting can apply lemon aromatherapy treatment to reduce nausea and vomiting so that they can reduce the use of pharmacological drugs that have side effects.